Educational Robotics as a Methodological Strategy for Improving School Performance in Mathematics - Spiess, Thiago Alessandro (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
In order to achieve the objective of developing computational thinking and logical reasoning among students at Escola de Ensino Fundamental Dr. Carlos Moritz, located in the city of Brusque, Santa Catarina, pedagogical tools were used, ranging from unplugged computing to the use of Chromebooks, interactive screen, Arduino kits and block programming platforms such as Scratch, Code.org and Robogarden. These tools brought programming language and educational robotics to the classroom. Furthermore, during school hours, a robotics club was offered to develop mechanical, electrical, and programming skills. In these Robotics classes, the school's dollhouse was transformed into a smart, sustainable house with a lighting sensor, solar panel, rainwater capture, and smart irrigation as a pilot proj ect at the end of 2021, which served as a starting point for developing new methodological strategies, in 2022, to improve student performance in the Mathematics curricular component. Furthermore, the school advanced in the use of technology in the classroom by creating a task force with teachers so that everyone felt comfortable using technology in the classroom.